THE DIVERSITY OF DISCERNMENT ON THE CONTROL ACCOUNTING GOVERNMENTAL - Flores Konja, Julio Vicente (2009)
The financial states, a means of periodic public management in ours showing, reflect several discernment of accounting control governmental, to side on the regulatory budget, then to agree at 77º article we ours Political Constitution , the public management at budget, the same is cash flow and dynamic ours of income and expense , is accountibily and reflecty to Financial States. For that reason, away of doctrine accounting governmental of “parallelism and simultaneous “, is appraisal in ours readyng of Financial States, we hope present work to take into consideration, the information financial in to General Accounts of Republic from 2006. The appreciations we exhibitions, to contribute at receive of critery unifications in to making and presentation from Financial States, that as the prescribe of International Accounting Standars of Governmental ( IAS-G ).